ASSESSMENT OF BIOLOGICAL ACTIVITY OF SELECTED SPECIES MUSHROOMS OF THE ORDER AGARICALES AND BOLETALES - PRODANOVIĆ, Nevena; KOSANIĆ, Marijana; KOČOVIĆ, Aleksandar; TOMOVIĆ, Jovica; MRKALIĆ, Emina; SOVRLIĆ, Miroslav (Studia Universitatis Babeș-Bolyai Chemia, 2023)
The aim of this study was to examine the antineurodegenerative, antimicrobial and antioxidant potential and to determine the total phenolics and total flavonoids of acetone extracts of selected mushrooms species (Suillus luteus, Leccinum aurantiacum, Agaricus xanthoderma and Tricholoma terreum) belonging to the genera Boletus and Agaricus. The content of phenolic components in the tested mushroom species varied in the total amount from 94.95 to 147.81 μg PE/mg extract, while the content of flavonoids varied in the range from 2.43 to 23.71 μg RE/mg extract. The tested acetone extracts showed acetylcholinesterase inhibition ranging from 11.49 to 17.46%. The strongest antimicrobial activity for the tested bacteria and fungi was shown by the species Agaricus xanthoderma. The antibacterial effect was stronger than the antifungal. Acetone extracts of the tested mushroom species showed moderate antioxidant activity. This study shows that the tested species of mushrooms possess different biological activity and that they can be used as a good source of natural agents are beneficial for human health.